BAIL 2008 - Boundary and Interior Layers Proceedings of the International Conference on Boundary and Interior Layers - Computational and Asymptotic Methods, Limerick, July 2008 - Hegarty, Alan.; Kopteva, Natalia.; O'Riordan, Eugene.; Stynes, Martin. (Lecture Notes in Computational Science and Engineering,, 2009)
This volume contains a wide-ranging cross-section of the papers presented at the BAIL 2008 conference, which was held from 28 July to 1 August 2008 at the University of Limerick, Ireland. The BAIL conferences are aimed equally at mathematicians (pure and applied) and engineers who share a common interest in the solution of problems that produce layer phenomena. Thus this book gives an excellent overview of current research into many engineering and mathematical problems of a singularly perturbed character.